Principle of progressively and strongly immobilizing polysulfides on polyoxovanadate clusters for excellent Li–S batteries application. (May 2020) - Yu, Ying; Li, Tianyu; Zhang, Hongzhang; Luo, Yang; Zhang, Huamin; Zhang, Jiangwei; Yan, Jingwang; Li, Xianfeng
Abstract: Sulfur-fixing materials have important effects on lithium-sulfur batteries application, but the principles and processes are not very clear yet. For the first time, we proposed the excellent performance of (NH4 )6 V10 O28 (NVO) clusters as sulfur-fixing materials and found that they have a unique two-step progressive sulfur-fixing mechanism. Firstly, the Li of lithium polysulfides (LiPSs) would attract the O of NVO cluster, which could widen the angle of O–V–O and expose the V atom inside the cluster. Secondly, the S of LiPSs can adsorb the V of NVO. The above progressive double interaction (Li–O and S–V) between NVO and LiPSs shows super strong binding energy (−423.41 to −627.19 kJ mol −1 ), which is 1.6 times higher than that of Li–O interactions only. It is also confirmed via both experimental test and DFT simulation. As a result, the Li–S batteries with NVO addition can deliver a reversible capacity of as high as 685 mAh g −1 at 1C. Even at a high sulfur loading of 6 mg cm −2, batteries showed a low decay rate of about 0.1% per cycle within 200 cycles at 0.1C. Graphical abstract: Image 1 Highlights: (NH4 )6 V10 O28 (NVO) as a super-double-strong fixative has highlighted the Li–S battery cycle performance. The interaction process between LiPSs and NVO was studied clearly. NVO and LiPSs show super strong binding energy (−423.41 to −627.19 kJ mol −1 ).